Community Theater Participation and Nutrition-Related Practices: Evidence from Nepal. Issue 4 (3rd April 2017) - Underwood, Carol R.; Broaddus, Elena T.; Kc, Shreejana; Thapa, Ravindra K.
Abstract : Suaahara, a nutrition-enhancement program in Nepal, conducted participatory community theater (CT) dramas with the goal of improving nutrition-related practices. To evaluate CT, a pre/posttest with randomized intervention and matched control sites was used. Dramas were conducted in Nawalparasi, Bajhang, and Sindhupalchowk Districts to represent the mountain, hill, and terai/plains regions. Within each study district, two intervention sites were randomly selected and two matched comparison sites were identified for inclusion in the study. At both baseline and endline, 600 individuals aged 18–59 (100 men and 100 women/district × 3 districts) were interviewed in the control sites and 600 in the intervention sites (1200 total respondents). Multivariate logistic analysis controlling for background characteristics found that CT attendance was significantly and positively associated with improved nutrition-related knowledge (adjusted odds ratio ratio [aORR] 10.2, p  < 0.001) and communication (aORR 2.4, p  < 0.001), hand washing after cleaning a defecating child (aORR 1.49, p  < 0.05), feeding children eggs (aORR 1.83, p  < 0.01), and feeding children meat and/or fish (aORR 2.10, p  < 0.01). This is the first study to rely on a pre/post matched intervention-control design to assess CT effects in a low-income setting. By testing the "difference-in-differences"—or the difference between intervention groups at baseline and endline minus that between controls at baseline and endline—the argument that the effects can be causally attributed to the intervention itself is strengthened. These findings support the continued and expanded use of CT to improve nutrition-related knowledge, communication, efficacy, and feeding practices as a valuable community-based, public health approach.